A Resistance to British Cultural Hegemony: Irish-Language Activism in West Belfast - Kachuk, Patricia (Anthropologica, 2022)
In this article it is to be argued that not all Irish-language activism in Belfast is revolutionary, but that rather, to use Williams' terminology, it has both alternative and oppositional ideologies as major components. While both alternative and oppositional Irish-language activists have recovered the Irish language and are using it to challenge the legitimacy of British cultural hegemony in Northern Ireland, the difference lies in their ultimate goals. The reaction of the British State to the challenge of Irish-language activists has varied depending on the form and perceived intent of Irish language activist groups. While prior to 1980, attempts were made to exclude the Irish language and culture from Northern Ireland, since 1989 the State's approach has been a re-interpretation of the Irish language and culture into the Northern Ireland context. Mixed reaction to the British government's efforts has resulted in an impasse.